THE DEVELOPMENT OF THE ISLAMIC INSURANCE (TAKAFUL) MARKET WITHIN THE NATIONAL ECONOMY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the development prospects of the Islamic takaful system within the insurance market of Uzbekistan. It highlights the opportunities offered by takaful, including strengthening trust in the financial sector, expanding customer  outreach, promoting financial inclusion, and supporting the growth of Islamic banking. At the same time, the study identifies key challenges hindering the sector’s expansion, such as low public awareness, underdeveloped digital infrastructure, and a shortage of qualified specialists. The findings indicate that the adoption of digital technologies and financial innovation plays a crucial role in advancing the takaful industry, enhancing its competitiveness, and ensuring its long-term sustainability within the national insurance market.
Keywords: Takaful; Islamic insurance; Uzbekistan insurance market; Financial inclusion; Islamic finance; Digital finance